DAYA TAHAN AEROBIK PADA ATLET SEKOLAH SEPAKBOLA USIA 14-16 TAHUN - Rika Sepriani (Jurnal MensSana, 2019)
The purpose of this research is to determine the level of aerobik endurance capability athletes global football school age 14-16 years old Payakumbuh city. This reseach used descriptive research approach. Population of this reseach is amounted 25 athletes. The technique of taked sampling is done by total sampling that all the population sampled with the number of 25 athletes. The data collection using by instrument yo-yo intermitten recovery test. Data analysis technique used is descriptive statistic technique with percentage counting. The results of this research is showed that 3 peoples (12%) were classified as moderate, 12 peoples (48%) were classified as less, and 10 peoples (40%) had aerobic endurance classified as poor. Conclusion of this reseach is the endurance ability of aerobic athletes global football age 14-16 years old Payakumbuh city is classified in poor cotegory.